Ajuba transactivates N‐cadherin expression in colorectal cancer cells through interaction with Twist. Issue 16 (26th June 2021) - Wu, Zhaoxia; Zou, Xiuqun; Xu, Ying; Zhou, Fengli; Kuai, Rong; Li, Ji; Yang, Daming; Chu, Yimin; Peng, Haixia
Abstract: Ajuba is a multiple LIM domain‐containing protein and functions as a transcriptional coregulator to modulate many gene expressions in various cellular processes. Here, we describe that the LIM domain of Ajuba interacts with Twist, and the Twist box is a pivotal motif for the interaction. Biologically, Ajuba enhances transcription of target gene N‐cadherin as an obligate coactivator of Twist. The enhancement is achieved by binding to the E‐box element within N‐cadherin promoter as revealed by luciferase reporter and chromatin immunoprecipitation assays. Mechanistic investigation demonstrates that Ajuba recruits CBP and Twist to form a ternary complex at the Twist target promoter region and concomitantly enhances histone acetylation at these sites. These findings identify that Twist is a new interacting protein of Ajuba and Ajuba/Twist/CBP ternary complex may be a potential treatment strategy for Twist‐related tumour metastasis.